Bryofloristic diversity and conservation value of a protected area in the Brazilian semi-arid region - Silva, Joan Bruno; Araújo Albuquerque, Karen Evellyn; de Brito Melo Trovão, Dilma Maria; de Faria Lopes, Sérgio (Phytotaxa, 2024)
We collected 137 samples (71—rainy season; 66—dry) for the Brazilian state of Paraíba. With a total of 23 species (one hornwort, 14 mosses and nine liverworts), we updated the bryoflora of Paraíba, a hotspot of bryophytes, by one rare species (Weissia controversa), increasing the total number of species to 188. The floristic composition in the Poeta e Repentista Juvenal de Oliveira State Park is affected by chronic anthropogenic disturbances, and is typical of arid environments, regardless of the season. This indicates homogenization of the habitat from the loss of ecological niche due to the disordered use of local natural resources. However, the record of Philonotis hastata, categorized as Near Threatened by the IUCN; the geographic expansion of a species; and the presence of rare species for Brazil reinforce the importance of the Conservation Unit for bryophyte biodiversity. Despite the floristic composition, we identified that interpretations about biology, environmental functionality and species distribution are more consistent for environmental assessment and decision-making on conservation actions.